2011
DOI: 10.1603/me11004
|View full text |Cite
|
Sign up to set email alerts
|

Population and Temperature Effects onLucilia sericata(Diptera: Calliphoridae) Body Size and Minimum Development Time

Abstract: Understanding how ecological conditions influence physiological responses is fundamental to forensic entomology. When determining the minimum postmortem interval with blow fly evidence in forensic investigations, using a reliable and accurate model of development is integral. Many published studies vary in results, source populations, and experimental designs. Accordingly, disentangling genetic causes of developmental variation from environmental causes is difficult. This study determined the minimum time of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 36 publications
0
58
1
1
Order By: Relevance
“…However, in our study only a single population was examined and the differences seen in time to developmental stage completion across temperature could be an example of environmental plasticity. Genetic variation in development time has been examined previously for L. sericata from several populations [3,30]. Gallagher et al [3] observed two populations from California, USA and one population from Massachusetts, USA in three environments (16. West Virginia flies exhibited significantly smaller larvae (length and weight) whereas California, USA larvae were larger, though all distributions exhibited considerable overlap with one another [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study only a single population was examined and the differences seen in time to developmental stage completion across temperature could be an example of environmental plasticity. Genetic variation in development time has been examined previously for L. sericata from several populations [3,30]. Gallagher et al [3] observed two populations from California, USA and one population from Massachusetts, USA in three environments (16. West Virginia flies exhibited significantly smaller larvae (length and weight) whereas California, USA larvae were larger, though all distributions exhibited considerable overlap with one another [31].…”
Section: Discussionmentioning
confidence: 99%
“…The need for development data for these forensically important species from various eco-regions is necessary as they might be significantly different [2,12]. Accounting for this variation could help reduce error associated with estimating a mPMI [30]. By researching different populations of flies and their ecological similarities and differences, forensic entomologists can partially explain the variation associated with the consumption phase of the postcolonization interval and infer a mPMI [5].…”
Section: Discussionmentioning
confidence: 99%
“…Improved biological knowledge of species from the blow fly (Diptera: Calliphoridae) genus Lucilia Robineau-Desvoidy, especially the sister species Lucilia sericata (Meigen) and Lucilia cuprina (Wiedemann), benefits basic (Singh and Wells 2013), medical (Greenberg 1973;Sherman 2009;Sherman et al 2000;Sherman and Pechter 1988), veterinary (Stevens and Wall 1996), and forensic science endeavors (Anderson 2000;Grassberger and Reiter 2001;Sze et al 2012;Tarone 2007;Tarone and Foran 2008;Tarone et al 2007;Tarone et al 2011). Since these species are primary colonizers of carrion, developmental data from these species can be useful for predicting the ages of immature blow flies associated with a body, which can help in estimating a minimum time of colonization for death investigations (Amendt et al 2007;Tomberlin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tous ces bénéfices associés au grégarisme permettent un développement optimisé des larves en limitant la prédation, le parasitisme ou la compétition et le risque de manque de ressources [19]. Partant de ces constats, l'hypothèse qu'il existerait pour chaque espèce une température préférentielle de développement, qui serait une température optimale pour un développement efficace tout en limitant la mortalité des larves, a été émise [20]. Cette tempé-rature permettrait également d'optimiser le succès reproducteur des insectes adultes [21].…”
Section: Comportement D'agrégation Des Insectesunclassified